2007
DOI: 10.1007/s00415-007-2016-3
|View full text |Cite
|
Sign up to set email alerts
|

Influences on cognition by immunosuppression and immunomodulation in multiple sclerosis

Abstract: Cognitive impairment is common also in early stages of MS, but only little is known about its relationship to standard immunotherapeutic drugs. Present data suggest that both immunosuppressive as well as immunomodulatory therapy prevent or delay the onset and severity of cognitive impairment although reversible cognitive deficits can occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Th is may be due to the partial ineff ectiveness of immunomodulatory treatment to correct recognition in MS patients compared to retrieval or it may be due to the type of immunomodulatory treatment which might have worsened cognitive function in MS patients. Few studies have shown that corticosteroids might worsen neuropsychological defi cit known to occur in early stages of disease (Tumani and Uttner 2007). Patients under steroid treatment were reported to have reversible impairment in long-term memory functions, whereas short-term memory and attentional functions remained unaff ected (Brunner et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Th is may be due to the partial ineff ectiveness of immunomodulatory treatment to correct recognition in MS patients compared to retrieval or it may be due to the type of immunomodulatory treatment which might have worsened cognitive function in MS patients. Few studies have shown that corticosteroids might worsen neuropsychological defi cit known to occur in early stages of disease (Tumani and Uttner 2007). Patients under steroid treatment were reported to have reversible impairment in long-term memory functions, whereas short-term memory and attentional functions remained unaff ected (Brunner et al 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Each disorder causing these syndromes will be addressed by investigation within the relevant research community, and preventive, medical, surgical, psychiatric, and rehabilitative interventions may all be relevant. Among many questions is whether immunosuppressive and immunomodulatory treatment in MS will effect cognitive improvement, as has been suspected (Fischer et al, 2000; Tumani and Uttner, 2007). Other promising therapeutic avenues for white matter disorders include bone marrow transplantation (Krivit et al, 1999), gene therapy (Leone et al, 2000), and stem cell therapeutics (Goldman, 2007; Tran et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Wegen des nachteiligen Einflusses einer GKS-Behandlung auf die kognitive Leistungsfähigkeit ist von einer neuropsychologischen Funktionsdiagnostik während und mindestens 8 -14 Tage nach der GKS-Gabe abzusehen. In mehreren Studien wurde gezeigt, dass sich immunmodulatorische Therapien im Krankheitsverlauf günstig auf die kognitiven Beeinträchtigungen auswirken können[43,92,93].Sowohl die Prävalenz von demenziellen Erkrankungen bei MS-Patienten als auch die Frage, ob diese infolge des neurodegenerativen Krankheitsgeschehens oder inwiefern diese koinzident auftreten, sind bislang nicht systematisch untersucht worden. Somit kann die bisherige Annahme, Demenzen seien bei MS selten, nicht mit belastbaren Daten belegt werden.…”
unclassified